2020
DOI: 10.48550/arxiv.2004.03624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relationship between Fully Connected Layers and number of classes for the analysis of retinal images

Ajna Ram,
Constantino Carlos Reyes-Aldasoro

Abstract: This paper experiments with the number of fully-connected layers in a deep convolutional neural network as applied to the classification of fundus retinal images. The images analysed corresponded to the ODIR 2019 (Peking University International Competition on Ocular Disease Intelligent Recognition) [9], which included images of various eye diseases (cataract, glaucoma, myopia, diabetic retinopathy, age-related macular degeneration (AMD), hypertension) as well as normal cases. This work focused on the classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…(3) We eliminated a few images that were marked as low image quality, however, these images are unavoidable in practical situations. (4) It was found out that the effect of increasing the number of fully-connected layers of a neural networks depends on the type of data set being used 42 , in our experiments, we found that in the convolution stage, the number of hidden dimensions also has a great impact on the recognition accuracy of fundus diseases, which is worth further study.…”
Section: Discussionmentioning
confidence: 69%
“…(3) We eliminated a few images that were marked as low image quality, however, these images are unavoidable in practical situations. (4) It was found out that the effect of increasing the number of fully-connected layers of a neural networks depends on the type of data set being used 42 , in our experiments, we found that in the convolution stage, the number of hidden dimensions also has a great impact on the recognition accuracy of fundus diseases, which is worth further study.…”
Section: Discussionmentioning
confidence: 69%
“…(3) We eliminated a few images that were marked as low image quality, however, these images are unavoidable in practical situations. (4) It was found out that the effect of increasing the number of fully-connected layers of a neural networks depends on the type of data set being used 28 , in our experiments, we found that in the convolution stage, the number of hidden dimensions also has a great impact on the recognition accuracy of fundus diseases, which is worth further study.…”
Section: Ablation Studymentioning
confidence: 69%
“…According to the statistics of 2019, over 2.2 billion people suffer from different eye diseases that result in serious vision impairment and partial or full blindness [1]. One of the main reasons for vision impairment is age-related macular degeneration (AMD).…”
Section: Introductionmentioning
confidence: 99%